2013
DOI: 10.1371/journal.pone.0068660
|View full text |Cite|
|
Sign up to set email alerts
|

High Weight Loss during Radiation Treatment Changes the Prognosis in Under-/Normal Weight Nasopharyngeal Carcinoma Patients for the Worse: A Retrospective Analysis of 2433 Cases

Abstract: BackgroundAlthough weight loss is common in nasopharyngeal carcinoma (NPC) patients receiving radiotherapy, the prognostic influence of weight loss and its impact modified by body mass index (BMI) are still unclear.Methods2433 NPC patients receiving radical radiotherapy at Sun Yat-sen University Cancer Center from November, 2000 to December, 2004 were enrolled. Weight change during radiation treatment was categorized into high weight loss (HWL) and low weight loss (LWL). The associations of HWL with overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 37 publications
8
66
2
1
Order By: Relevance
“…If a patient is severely malnourished, the treatment choice should be surgery, not RT or CRT. This is supported by the observation that rapid weight loss during RT is associated with a worse prognosis, and patients with a lower BMI may be more vulnerable to weight loss than those with a higher BMI. However, although poor nutritional status in surgically treated patients increases the risk of complications, it does not affect the oncologic outcome.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…If a patient is severely malnourished, the treatment choice should be surgery, not RT or CRT. This is supported by the observation that rapid weight loss during RT is associated with a worse prognosis, and patients with a lower BMI may be more vulnerable to weight loss than those with a higher BMI. However, although poor nutritional status in surgically treated patients increases the risk of complications, it does not affect the oncologic outcome.…”
Section: Discussionmentioning
confidence: 84%
“…We could not include weight loss as a nutritional parameter because of lack of data. Recently, Shen et al showed that BMI combined with weight change during treatment was superior to BMI alone in predicting the survival of patients with nasopharyngeal cancer. We should therefore include both BMI and weight change in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to maintain weight in cancer patients during the treatment period. Although unplanned weight loss among those not receiving nutrition via prophylactic PEG tubes appeared to be temporary and reversible in the ensuing recovery period, others have demonstrated that loss of >5% of baseline body weight during radiation treatment may decrease the efficacy of treatment 2729. Unfortunately, survival differences between both groups cannot be assessed here due to the relatively short follow-up time.…”
Section: Discussionmentioning
confidence: 89%
“…According to the previous reports (Qiu et al 2011;Ravasco et al 2005;Capuano et al 2008;Shen et al 2013), malnutrition before and during treatment has been identified as a risk factor predicted worse outcome in head and neck cancer or NPC patients due to severity of acute toxicities, decreasing chemotherapy dose intensity, interruption of treatment, reducing the radiosensitivity and/ or chemosensitivity of tumour and compromised immunity. Although no delay or interruption of radiotherapy, or chemotherapy dose intensity reduction was observed in all patients in this study, we supposed that the nutritional status steadily deteriorated during CCRT in the patients with low PNI subgroup result in lower survival rates by reducing radiosensitivity and/or chemosensitivity, and compromised immunity.…”
Section: Discussionmentioning
confidence: 99%